Kontribusi Dana Desa, Lembaga Keuangan Syariah, dan Integrasi Ekonomi Regional terhadap Pertumbuhan Ekonomi - Putri Amirah Hajarani; Imsar Imsar (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2025)
This study aims to analyze the contribution of village funds, Islamic financial institutions, and regional economic integration to regional economic growth. In the context of fiscal decentralization and regional development, these three variables play a strategic role in accelerating inclusive and sustainable economic development. Village funds serve as the primary instrument to finance infrastructure development and community empowerment. Meanwhile, Islamic financial institutions provide access to fair and Sharia-compliant financing, supporting the productivity of micro and small enterprises. Regional economic integration, particularly through inter-regional connectivity and cooperation, strengthens local markets and enhances regional competitiveness. The analysis method uses a descriptive-qualitative approach based on literature studies and secondary data. The findings indicate that the synergy among the three variables can drive equitable economic growth, although integrated policies and institutional capacity strengthening are still needed.